The predictive value of carotid artery strain and strain-rate in assessing the 3-year risk for stroke and acute coronary syndrome in patients with metabolic syndrome. (3rd October 2022) - Arnautu, D A; Vacarescu, C; Arnautu, S F; Gaita, L; Cozma, D; Gaita, D
Abstract: Purpose: The goal of this study is to see if carotid strain and strain rate can predict major cardio-vascular events (MACE) in people who have metabolic syndrome (MS) over a 3-year period of time. Methods: In this prospective observational research, we enrolled 220 adult MS patients (60.7±7.5 years old, 53% male). Bilateral 2D common carotid carotid artery (CCA) speckle-tracking ultrasound was used to determine the peak circumferential strain (CS) and the peak circumferential strain rate (CSR). Clinical outcomes were assessed throughout a three-year follow-up period. Results: After a 3-year follow-up period follow-up, 14 (7%) experienced MACE: Eight (4%) suffered an atherothrombotic ischemic stroke, four (2%) had acute coronary syndrome, and two (1%) were hospitalized for heart failure. Univariate regression analysis of the clinical and echocardiographic features of the MS patients found that age, systemic hypertension, diabetes mellitus, and the CCA circumferential strain and strain rate were significantly associated with the risk of MACE. Multivariate logistic regression identified two independent predictors of MACE in patients with MS, namely the CCA-related CS (%) and CSR (1/s), P<0.01. The ROC curve analyses of these independent predictors of MACE indicated appropriate sensitivities and specificities. CS (AUC = 0.806, sensitivity = 82.6%, specificity = 79.2%, P<0.0001); CSR (AUC = 0.779, sensitivity = 82.6%, specificity = 72.4%, P<0.0001). The cut-off values were ≤2.9% for carotid CS and ≤0.35 s –1 for carotid CSR. Using these cut-off values, we obtained Kaplan-Meier survival curves, and these showed that MACE, ischemic stroke, and ACS-free survival was significantly lower among the MS patients with lower carotid CS and CSR (P<0.0001). Conclusion: Carotid CS and CSR were independent predictors of major cardio- and cerebrovascular events in prospectively monitored MS patients without established cardiovascular disease. Carotid deformation could be valuable as an early prognostic indicator for the cardiovascular risk in this population group. Funding Acknowledgement: Type of funding sources: None.